PENGARUH TOTAL ASSET TURNOVER, LEVERAGE DAN SALES TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Candradevi, Astiani Nur; Alliyah, Siti (Jurnal Riset Akuntansi Politala, 2024)
This study aims to determine the impact of Total Asset Turnover, Leverage, and Sales on profit growth in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period of 2019 - 2021. The sampling technique employed was purposive sampling, resulting in a sample size of 11 companies. For this study, the data analysis method employed is multiple linear regression analysis. The findings of this study indicate that Total Asset Turnover and Sales have a positive impact on profit growth, whereas Leverage has a negative impact on profit growth.